Electronic style : a guide to citing electronic information - Li, Xia, 1964- (Meckler, 1993)
While electronic sources are revolutionizing and reshaping patterns of scholarly interaction, no work has addressed the issues of citing electronic documents. "Electronic Style: A Guide to Citing Electronic Information" standardizes citation methods for the complete range of electronic formats, including full-text information files, bibliographic databases, Internet-accessible electronic journals and discussion lists, email, bulletin board systems, and commercial online documents--Back Cover.